2013
DOI: 10.1371/journal.pone.0070675
|View full text |Cite
|
Sign up to set email alerts
|

Role of PPARα and HNF4α in Stress-Mediated Alterations in Lipid Homeostasis

Abstract: Stress is a risk factor for several cardiovascular pathologies. PPARα holds a fundamental role in control of lipid homeostasis by directly regulating genes involved in fatty acid transport and oxidation. Importantly, PPARα agonists are effective in raising HDL-cholesterol and lowering triglycerides, properties that reduce the risk for cardiovascular diseases. This study investigated the role of stress and adrenergic receptor (AR)-related pathways in PPARα and HNF4α regulation and signaling in mice following re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 65 publications
1
18
1
1
Order By: Relevance
“…HNF4A is a master metabolic regulatory factor responsible for the activation of the hepatic gluconeogenesis (16) and has been implicated in diabetes, inflammation, and lipid metabolism (17)(18)(19)(20)(21). In this context, diabetes has been associated with PD in numerous epidemiological studies (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…HNF4A is a master metabolic regulatory factor responsible for the activation of the hepatic gluconeogenesis (16) and has been implicated in diabetes, inflammation, and lipid metabolism (17)(18)(19)(20)(21). In this context, diabetes has been associated with PD in numerous epidemiological studies (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was identified that hepatocyte nuclear factor-4α (HNF-4α) was a highly conserved member of the nuclear receptor superfamily, which was initially identified as a transcriptional factor required for liver-specific gene expression, and it was also critical in regulating the transcription of genes involved in glucose and lipid metabolism including APOA5 [20]. Intriguingly, previous study reported that HNF-4α and PPARα expression could be activated by hepatic protein kinase A (PKA) pathway [21]. More interestingly, it was reported that hepatic GPR30 combined with estrogen and in turn exerted its function by activating PKA pathway [18].…”
Section: Presentation Of the Hypothesismentioning
confidence: 99%
“…The present data indicate that stimulation of α 1 ‐ or β 1/2 ‐AR can efficiently reduce serum TRL levels via stimulation of TG hydrolysis, transport, metabolism and clearance, as well as inhibition of hepatic TG synthesis. Given that stress response includes adrenοceptor stimulation, our data further support that the stress‐induced changes in serum TG levels are mediated by α 1 ‐ and β 1/2 ‐ARs in a PPARα‐independent fashion, further supporting that PPARα activators, such as fibrates, may not be effective in the treatment of stress‐related hypertriglyceridemia. Additional research may identify these PPARα‐independent triggers providing alternative pharmacological targets for new pharmacological entities that may complement current therapies.…”
Section: Resultsmentioning
confidence: 52%
“…Despite these developments, the molecular triggers that are associated with the disease development and eventually with the elevated plasma, TRL accumulation remain largely unexplored. There is a strong evidence that both, central and peripheral nervous systems, may be involved in this regulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation